2017
DOI: 10.1007/s40477-017-0265-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-time elastography for the detection of fibrotic and inflammatory tissue in patients with stricturing Crohn’s disease

Abstract: MSR detection was not able to distinguish fibrotic from inflammatory tissue in our selected population. This result could be influenced by the presence of the superimposed inflammation. Larger cohort of patients, further analysis with shear wave elastography, and validated histopathology classification systems for fibrosis and inflammation are necessary to assess if intestinal fibrosis could be reliably detected on the basis of bowel elastic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 40 publications
(40 reference statements)
0
72
1
Order By: Relevance
“…1). Eventually, a total of 6 studies consisting of 4 full text articles [14,25,26,39] and 2 abstracts [41,42] met the eligibility criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). Eventually, a total of 6 studies consisting of 4 full text articles [14,25,26,39] and 2 abstracts [41,42] met the eligibility criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…▶ Table 1 shows the characteristics of the included studies. Only three studies reported the mean age of the participants and the proportion of men [25,26,39]: the mean age ranged from 35.5 years [25] to 46.1 years [26] and the proportion of men from 33.3 % [26] to 61.5 % [25]. One study included both humans and animals, but only the data regarding humans were considered [14].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though there is little data available, the first results in this direction are promising, suggesting the ability of elastography to differentiate between inflammatory and fibrotic tissue, which is crucial for the management of these patients [95][96][97][98]. Fibrosis develops in time as a consequence of chronic inflammation and has a major influence on IBD morbidity, as it is associated with high rates of hospitalization and surgical interventions [99].…”
Section: Elastographymentioning
confidence: 99%